Marketplace dan dropshipping dalam perspektif fiqih bisnis online halal - Mubarok, Azmi sahlul (Maliki Interdisciplinary Journal, 2026)
The development of the digital economy has drastically transformed the global trade system. Business models such as marketplaces and dropshipping have become popular innovations that enable fast transactions without the need for physical ownership of goods. However, from a fiqh muamalah perspective, these practices need to be reviewed to ensure their compliance with Sharia principles, which reject riba (usury), gharar (uncertainty), and maisir (speculation). This article aims to examine the marketplace and dropshipping systems in depth based on Islamic law using a literature review approach from several academic journals, including works by Ahmad Djalaluddin, Dini Rahmatina, Muhammad Anugrah, and the views of contemporary scholars such as Shaykh Sa’ad bin Turki Al-Khotslan. The study’s results indicate that marketplaces are essentially halal as long as the contract is clear and transparent, while dropshipping is permissible if it uses the wakalah bil ujrah or salam muqayyad contract, with strict supervision of the seller’s honesty and responsibility.